Newsprint Grade Ground-wood Pulps from Alnus nepalensis - Guha, S. R. D.; Singh, Man Mohan; Kumar, Krishan (Indian Forester, 1965)
Laboratory Experiments on the production of ground-wood pulps from Alnus nepalensis are described. Standard pulp sheets are made from 100 per cent ground-wood pulp from this species and from a mixture of 60 per cent ground-wood pulp and 40 per cent imported bleached sulphate pulp. The strength properties and brightness of standard sheets prepared from the ground-wood pulp under suitable condition have shown that this wood is a suitable raw material for the production of ground-wood pulp suitable for newsprint production.